From map to horizon; from trail to journey: Documenting Inuit geographic knowledge - Aporta, Claudio (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2005)
AbstractThis paper describes how new cartographic and information technologies were used to record and represent Inuit geographic and environmental knowledge in Igloolik, Nunavut. The method proved a powerful tool to document an approach to geography that is mainly oral. It was also helpful in documenting how people relate to a highly dynamic environment as the Arctic. The method includes the merging of different geographic databases that acquire full meaning when seen as layers of the same map. It also involves the search for new ways of representing, including simulated horizons, photographs of horizons embedded on maps, and recordings of oral descriptions of trails and locations. An example of such method can be seen in the Igloolik Multimedia Project, a CD-Rom that is being currently piloted in the Igloolik high school.